Effects of secukinumab on synovitis and enthesitis in patients with psoriatic arthritis: 52-week clinical and ultrasound results from the randomised, double-blind ULTIMATE trial with open label extension - D'Agostino, Maria Antonietta; Carron, Philippe; Gaillez, Corine; Conaghan, Philip G.; Naredo, Esperanza; López-Rdz, Alejandra; Šenolt, Ladislav; Burgos-Vargas, Ruben; Hanova, Petra; Padovano, Ilaria; Cazenave, Tomas; Stoenoiu, Maria S.; et al. (Seminars in Arthritis and Rheumatism, 2023)
Objectives: In the ULTIMATE study with an open label extension, we assessed the long-term effect of secukinumab at tissue level on synovitis and enthesitis, and across all psoriatic arthritis (PsA) manifestations, using both clinical evaluations and power Doppler ultrasonography (PDUS). Methods: This randomised, placebo-controlled, Phase 3 study (ULTIMATE) included biologic-naïve patients with PsA with active PDUS synovitis and clinical enthesitis, and inadequate response to conventional synthetic disease-modifying antirheumatic drugs. The study consisted of 3 treatment periods; in the first period (baseline to week 12) patients were randomised to receive subcutaneous secukinumab (150 mg or 300 mg according to severity of skin psoriasis) or placebo every week until week 4 and once every 4 weeks up to week 12. In the second period (weeks 12–24) all patients received open-label secukinumab with placebo patients switching to secukinumab (150 mg or 300 mg). The third period (weeks 24–52) was an extended open-label treatment period. The long-term responsiveness of the Global EULAR-OMERACT Synovitis Score (GLOESS), clinical enthesitis and global PDUS-detected enthesitis score (using two candidate definitions of activity) at patient level, together with clinical efficacy across key manifestations of PsA and safety were assessed. Results: Of the 166 patients enrolled, 144 completed week 52. A significant reduction in GLOESS was demonstrated in the secukinumab group vs placebo at week 12, followed by a stable reduction of synovitis until week 52 in the secukinumab group while placebo switchers from week 12 reached a similar level of reduction at week 24 with stability thereafter. Likewise, a significant reduction in the Spondyloarthritis Research Consortium of Canada (SPARCC) enthesitis index was shown in the secukinumab group vs placebo at week 12 with sustained improvement to week 52. Global OMERACT PDUS enthesitis scores were numerically lower in secukinumab vs placebo switchers in the first two treatment periods, with some stability in the third period in both groups. Improvements in clinical responses were also observed across all key domains of PsA up to week 52 in both treatment groups with no new or unexpected safety signals. Conclusions: ULTIMATE showed consistent improvements in clinically and ultrasound-assessed synovitis and enthesitis and sustained clinical efficacy through week 52 in patients with PsA treated with secukinumab and placebo switched to secukinumab.
CRIS-Team Scopus Importer:2023-09-15
Keywords: Clinical response; Enthesitis; OMERACT; Power Doppler ultrasonography; Psoriatic arthritis; Synovitis